Contribution of epidermal growth factor (EGF) in the treatment of cutaneous leishmaniasis caused by Leishmania major in BALB/c mice. - Mohammad Saberi; Alireza Latifi; Majid Golkar; Pezhman Fard-Esfahani; Sina Mohtasebi; Aref Teimouri; Mohammad Javad Abbaszadeh Afshar; Elham Kazemirad; Mehdi Mohebali; Mehdi Mohebali (PLoS Neglected Tropical Diseases)
Cutaneous leishmaniasis (CL) is a tropical disease that can cause chronic lesions and leave life-long scars, leading to social stigmatization and psychological disorders. Using growth factors and immunomodulatory agents that could accelerate wound healing and reduce the scar is highly demanded. Epidermal growth factor (EGF) plays an essential role in wound healing. It stimulates the proliferation of keratocytes and fibroblasts, and promotes re-epithelialization. Here, the effect of EGF in combination with Glucantime and nano-liposomal Amphotericin B (SinaAmpholeish) on the healing process of CL in BALB/c mice was investigated. Seventy-two mice were infected with Leishmania major parasites and randomly divided into eight treatment groups after the appearance of the lesion. The treatment was continued for five weeks, and lesion sizes were measured weekly. Parasite load was determined in the skin biopsies using qPCR. We found that subcutaneous injection of EGF at 4.5 μg/kg, combined with each of the two antileishmanial drugs, significantly reduced the wound size and parasite load; however, EGF at 1.5 μg/kg failed to be effective. Besides, the wound size and parasite loads were significantly lower in the SinaAmfoleish groups compared to the Glucantime groups. Among the treatment groups, EGF 4.5 μg/kg combined with SinaAmpholeish exhibited the most significant reduction in wound size and parasitic load. Our results suggest that EGF can potentiate the wound healing effect of antileishmanial drugs. Further studies are warranted to explore the beneficial effects of combining EGF with antileishmanial drugs in patients with cutaneous leishmaniasis in order to accelerate wound healing and reduce the scar.